Pengembangan Modul Elektronik Flipbook Materi Haji Dan Umrah Pada Pembelajaran Fiqh - Elza Salmawati; Fadriati Fadriati (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2022)
It is discovered that educators have not used flipbook electronic modules in the study of Jurisprudence (Fiqh). They only utilize textbooks that are boring and make it harder for students to grasp the subject. The design of the textbook is unattractive, and it lacks the necessary information to inspire students to learn. The textbooks should include a thorough description of the subject matter, be visually attractive and colorful, and match the subject matter in the provided pictures. This electronic flipbook module was developed with the intention of increasing students' willingness to alter their thought processes and understand logical concepts for the benefit of successful learning. By utilizing a 4D model, this study engaged in research and development (R and D) (define, design, develop and disseminate). Data came from eighth-grade students and Fiqh teachers. Validation sheets, interviews, and observations were all types of data collection tools. The developed modules were then evaluated for validity and degree of applicability. After gathering the data, its validity and applicability were evaluated. Based on validation results, it was determined that the electronic flipbook module was valid with the score 80.278%. While, the practicality was in a highly valid category with the score 97.44%. This flipbook electronic module can be utilized as Hajj and Umrah learning resources in Fiqh subject based on the findings of the validation and practicality tests.